The political economy of food price policy: Country case study of Mozambique - Virgulino Nhate; Claudio Massingarela; Vincenzo Salvucci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The 2007-09 price shocks affected in particular the prices of food commodities and fuel. As a consequence, Mozambique experienced reduced exports, more expensive imports and increased food and oil prices, contributing to the stagnant poverty rates registered in 2008/9. Our analysis finds, first, that domestic prices for imported food crops followed the international trends only partially and remained high even after international prices declined. And second, the policy responses adopted by the Mozambican government to stabilize the impact of price shocks in the domestic market seem to have been effective, even though they turned out to be costly in terms of lost revenue and increased debt.
Keywords: E31; F42; E64; 330; food price; agriculture; price shocks; political economy; Mozambique; Lebensmittelpreis; Lebensmittelpreis; Ernährungssicherung; Schock; Mosambik